Um modelo de simulação discreta para analisar o sistema integrado de colheita de cana-de-açúcar e aproveitamento de biomassa - Silva, João Eduardo Azevedo Ramos da (2011)
Brazil is one of the greatest sugarcane producers of the world, with figures that exceeds 620 million tons in 2010/2011 harvest season. There is an expectation of strong increase of Brazilian sugarcane production in next years due to increase in sales estimulated by the low production cost of sugar and alcohol and also the increase of the internal and external demands for ethanol, in substitution to fossil fuels. At the same time, environmental issues led the publication of a specific legislation that established a schedule to the next years to stop sugarcane burning previous to hand cutting, a traditional activity. This legal restriction brought a new scenario, as an increasing amount of biomass, that used to be burnt, will be available for other uses such as ethanol extra production, by technologies still in development or to energy generation, similar to what is done with bagasse (by means of cogeneration). Independent of its use, sugarcane and its biomass processing configures a complex operation as big volumes of materials are handled using high cost equipment which a high interaction among them. Several systems can be configured to do this task, varying equipments and settings of the operations performed by them. The selection of equipment and operational proceedings is one of the main tasks of managers at sugarcane mills. In order to help in decision taking situations, in this study, a discrete event simulation model was designed and modeled to represent sugarcane harvesting systems with biomass recovery. Conventional sugarcane harvesting and partial cleaning sugarcane harvesting were represented in a unique simulation model, as well as the correspondent alternatives of biomass recovery and delivery at mills. The operational characteristics of these systems were previously set in the model and can be modified through electronic spreadsheets, interfaced with the simulation model that manages the input and output of data. Field tests were done to evaluate equipment performance and generate data to the simulation model, which was used in two studies. In the first study, three sugarcane harvesting and biomass recovery systems were simulated using the data collected at each field test, representing those systems differently, under their own observed conditions. In the second study, the three systems were again compared, however, under the same conditions, with the same set of assumptions, in order to permit their comparison in equal basis. All scenarios considered a typical mill operation that processes two million tons of sugarcane per harvest season. The simulation model enabled the evaluation of the selected systems considering sugarcane and biomass production as well as their economic evaluation.